Residual Herbicide Programs With Multiple Sites-of-action Improved Weed Control in Grain Sorghum - Olumide S. Daramola; K.B. Jeremie Kouame; Taylor Lambert; Matthew Vredenburg; Atong A. Akom (Kansas Agricultural Experiment Station Research Reports, 2025)
A strong preemergence herbicide program is an essential best management practice for multiple herbicide-resistant weeds. Palmer amaranth is a prolific seed producer that has evolved resistance to 6 herbicide sites-of-action in Kansas. The objective of this study was i) to evaluate the effectiveness and crop safety of residual herbicide programs with single and multiple sites-of-action used for weed control in no-till dryland grain sorghum production systems of western Kansas and ii) the impact of lowering the rate of Callisto in mixture with Dual II Magnum on weed control in no-till dryland grain sorghum production systems of western Kansas. Results showed that the preemergence herbicide treatments controlled Palmer amaranth (96-100%), puncturevine (93-100%), and large crabgrass (96-100%) 22 days after application. However, control of these weeds decreased at 43 days after treatment, with atrazine providing the least control (63-70%) compared to other herbicide combinations, including FulTime NXT, Calibra, atrazine + Calibra, Verdict + Outlook, or Dual II Magnum + Callisto (83-100%). Sorghum injury ranged from 1.3% to 17% 15 days after treatment, but sorghum recovered with injury levels of 7% or less at 43 days after treatment. The Dual II Magnum + Callisto combinations resulted in higher yields (92-94 bu/a) compared to the untreated control (69 bu/a). The results suggest that the herbicides evaluated can be safely applied to sorghum for weed control under favorable environmental conditions. Higher rates of Callisto in combination with Dual II Magnum did not offer additional weed control benefits compared to the lower rates used in this trial. Regardless of application rates, herbicide programs incorporating active ingredients targeting multiple sites-of-action resulted in improved weed control compared to those targeting a single site-of-action. Therefore, these herbicide programs can help minimize Palmer amaranth escapes and prevent the replenishment of the soil seedbank.
Keywords: crabgrass; Palmer amaranth; residual herbicides; sorghum yield